Higher Expression of Lympho-epithelial Kazal-type-Related Inhibitor-1 Fragments and Decreased Desquamation in the Lesional Skin of Nummular Eczema - Montenegro, Sara Estefania; Oh, Jang-Hee; Suh, Joong Heon; Mun, Je-Ho; Chung, Jin Ho (Acta dermato-venereologica, 2024)
Nummular eczema, a chronic dermatitis characterized by coin-shaped lesions, was first documented in 1857. However, its pathophysiological characteristics are still not well known. To investigate differences in the regulation of the desquamation process in the stratum corneum of lesional and nonlesional skin of patients with nummular eczema and healthy control subjects, tape-stripped stratum corneum samples from patients with nummular eczema and healthy volunteers were analysed using immunofluorescence staining and western blot analysis. In the nummular eczema lesional skin, expression of desmoglein-1, desmocollin-1, and corneodesmosin exhibited a disorganized, dense or partially diffuse non-peripheral pattern with increased intensity, compared with the peripheral patterns observed in healthy or nonlesional skin, suggesting the impaired desquamation process in nummular eczema. Furthermore, although the expression of the desquamation-related serine proteases, kallikrein-related peptidase 7 and 5, was increased in nummular eczema lesional skin, the immunofluorescence staining of lympho-epithelial Kazal-type-related inhibitor-1, an endogenous inhibitor of various kallikrein-related peptidases, and its fragments were significantly increased in the nummular eczema lesional skin, suggesting its contribution to the inhibition of corneodesmosomal degradation. Therefore, the increased detection of corneodesmosomal proteins in nummular eczema lesions may be due to the increased amount of the fragments of lympho-epithelial Kazal-type-related inhibitor-1, which could contribute to delayed desquamation.